The "Arab Wave" in World Music after 9/11 - Swedenburg, Ted (Anthropologica, 2022)
This paper investigates the paradoxical surge in popularity of Arab music, post 9/11, in the U.S. world music scene. It charts the gradual incursion of Arab popular music into the U.S. from the late 1980s, showing how this was on the one hand, a progressive phenomenon, given U.S. antipathy toward Arabs and Islam, and on the other, that such gains were won through the deployment of anti-fundamentalist and exoticising discourses. In the post-9/11 period, Arab music has entered the U.S. at a time of both increased public hostility and interest toward Arabs and the Middle East. The heightened popularity of Arab music has arguably been a source of pride for Arab-Americans and a means of creating more acceptance for Arab culture in the U.S. Whether the growing marketability of Arab music will have significant progressive consequences, however, will depend on the nature of political mobilization on Middle East issues in the U.S. and how that activity is aligned with cultural practice.